Pain quality patterns in delayed onset muscle soreness of the lower back suggest sensitization of fascia rather than muscle afferents: a secondary analysis study: sensory physiology - Brandl, Andreas; Wilke, Jan; Egner, Christoph; Schmidt, Tobias; Schilder, Andreas; Schleip, Robert (Pflügers Archiv, 2024)
Delayed onset muscle soreness (DOMS) of the lower back is considered a surrogate for acute low back pain (aLBP) in experimental studies. Of note, it is often unquestioningly assumed to be muscle pain. To date, there has not been a study analyzing lumbar DOMS in terms of its pain origin, which was the aim of this study. Sixteen healthy individuals (L-DOMS) were enrolled for the present study and matched to participants from a previous study (n = 16, L-PAIN) who had undergone selective electrical stimulation of the thoracolumbar fascia and the multifidus muscle. DOMS was induced in the lower back of the L-DOMS group using eccentric trunk extensions performed until exhaustion. On subsequent days, pain on palpation (100-mm analogue scale), pressure pain threshold (PPT), and the Pain Sensation Scale (SES) were used to examine the sensory characteristics of DOMS. Pain on palpation showed a significant increase 24 and 48 h after eccentric training, whereas PPT was not affected (p > 0.05). Factor analysis of L-DOMS and L-PAIN sensory descriptors (SES) yielded a stable three-factor solution distinguishing superficial thermal (“heat pain “) from superficial mechanical pain (“sharp pain”) and “deep pain.” “Heat pain “ and “deep pain” in L-DOMS were almost identical to sensory descriptors from electrical stimulation of fascial tissue (L-PAIN, all p > 0.679) but significantly different from muscle pain (all p < 0.029). The differences in sensory description patterns as well as in PPT and self-reported DOMS for palpation pain scores suggest that DOMS has a fascial rather than a muscular origin.
Gesehen am 07.02.2024